Savira's Magical Body Pop-Up Book - Savira Agnisa; Wahyu Taufiq (Jurnal Pendidikan Anak Usia Dini, 2026)
Savira's Magical Body Pop-Up Book is an interactive educational tool designed for elementary school students to explore the fascinating world of body parts while enhancing their English language skills. This engaging pop-up book features vibrant visuals and three-dimensional elements that captivate young learners and make the learning process enjoyable and effective. Each page contains dynamic pop-up illustrations of different body parts, beginning with a full-length view of the human body, and is accompanied by interactive exercises that promote active participation. The structured content includes an introduction to the human body, detailed explorations of the head, upper body, and lower body, along with interactive labeling activities. Research supports the effectiveness of multisensory approaches in improving retention and understanding, making this book a holistic learning experience. By employing various interactive strategies and activities, students can visualize, label, and engage with the material, ultimately fostering a deeper understanding of their bodies and the related vocabulary.